Human Rights, Popoki and Bare Life - Alexander, Ronni (In Factis Pax: Journal of Peace Education and Social Justice, 2009)
The theme of this year’s IIPE was ‘Human Rights Learning as Peace Education: Pursuing Democracy in a Time of Crisis,’ and participation gave me an opportunity to explore further the relationship between human rights learning and my work for peace with the Popoki Peace Project. In particular, it raised questions about human rights and human rights learning in the context of the so-called “zones of exception,” those bare life zones and “othered” places that provide evidence for governments and concerned citizens alike that good governance and democracy are necessary and desirable. Some scholars suggest that NGOs and others engaged in humanitarian action play an important role in the creation of such zones, although one can hardly think they do so ntentionally. (See for example Duffield, 2008). In our commitment to human rights learning, do we fall into that category? In reflection, I realized that if we are to engage in critical human rights learning, we need to be critical of ourselves and the way humanitarian efforts, our own included, often serve to replicate many of the contradictions they seek to solve.